Microplastic identification and quantification from organic rich sediments: A validated laboratory protocol - Vermeiren, P.; Muñoz, C.; Ikejima, K. (Environmental pollution (1987), 2020)
Plastic pollution presents a global environmental concern with potentially widespread ecological, socio-economic and health implications. Methodological advances in microplastic extraction, quantification and identification from sediments have been made. However, integrating these fragmentary advances into a holistic, cost-effective protocol and applying it to organic rich sediments with fine grain size remains a challenge. Nonetheless, many hot spots of microplastic contamination such as harbour and estuarine sediments are characterised by such sediments. We conducted a series of experiments to integrate methodological advances, and clarify their applicability to organic rich sediments with fine grain size. The resulting protocol consisted of three stages. First, pre-treatment with Fenton’s reagent was found to be efficient in reducing organic matter content, compatible with later Fourier Transform-Infrared Spectroscopy (FT-IR) for polymer identification, although it did affect the size of polyethylene (PE) and polyethylene terephthalate (PET). Secondly, a novel density separation column with a top overflow (the OC-T) obtained recovery rates above 90% for microplastics present in a ZnCL2 solution. Finally, automated epifluorescence microscopic image analysis of Nile Red stained filters with selected validation of polymer identities using FT-IR revealed 91.7% of stained particles to be plastics. A case study on estuarine sediments demonstrated a high extraction efficiency with quantification possible down to 125 μm and detection possible down to 62.5 μm. This makes this protocol suitable for large scale monitoring of microplastics in sediments of estuarine origin provided polymer specific recovery rates, background contamination and uncertainty in Nile Red identification is accounted for. Subject to further validation, the protocol could also offer a solution to similar organic rich sediments with fine grain size, such as some soils and sludge, to improve our ability to conduct cost-effective, large scale monitoring of microplastic contamination. [Display omitted] •Methodological advances were integrated into a holistic microplastic lab protocol.•The protocol targets cost-effective, large scale monitoring of microplastic pollution.•A new density separation column (OC-T column) obtained high extraction efficiency.•Validation of Nile Red fluorescent stained particles revealed 91.7% to be plastics.•Microplastic quantification down to 125 μm was possible in an estuarine case study. We developed a three-stage protocol, integrating current fragmentary methodological advances for microplastic extraction, identification and quantification. A combination of fluorescent quantification with selected polymer identification for particles down to 125 μm makes this protocol suitable for cost-effective, repeatable, large scale monitoring of microplastic contamination in organic rich sediments.